Alans in Mongol Service in First Third of 13th Century - E. V. Kaziev (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
The author considers actual and, despite the presence of a number of written medieval sources and a wide consideration of the topic in scientific literature, discussion questions about the Alans who were in the service of the Mongol Kaans and emperors of the Yuan dynasty, and about the time of the first appearance of the Alans in the Mongol service. The novelty of this study lies in the fact that the question of establishing the time of the first appearance of the Alans in the service of the Mongols is solved in it through determining the time of the introduction of Mongol rule in the territory of the Ciscaucasia. Particular attention is paid to the analysis and correlation of information from the main medieval written sources about this event: Mongolian, Persian, Arab and Khorezm. The result of the study was the conclusion that the raid of the Mongol commanders Jebe and Subeday in the Ciscaucasia did not have any political consequences for Alania, and the information from written sources reporting that the Alans became part of the Jochi ulus in 1224 is either a form of a declaration about the intentions of the Mongol house that ruled at that time, or late chronicle inserts reflecting the state of affairs that developed after the Western campaign of the Mongols.